Pengaplikasian Warna Sekunder dengan Teknik Makeup Bold terhadap Hasil Tata Rias Pesta - Salsabila Qurratul Aisyu; Dindy Sinta Megasari; Maspiyah; Dewi Lutfiati (Program Studi Pendidikan Tata Rias, 2024)
The makeup trend using secondary colors is increasingly popular among beauty lovers, offering interesting and creative variations to create a standout look. The bold makeup technique aims to be a bold, striking, and eye-catching look, especially for special occasions such as parties. The purpose of this study is first, to determine the difference in party makeup results using secondary colors (X1 (orange-orange-orange), X2 (purple-purple-purple), X3 (green-orange-purple)) with the bold makeup technique. Second, to determine the highest and lowest values ​​between X1 (orange-orange-orange), X2 (purple-purple-purple), X3 (green-orange-purple) with the bold makeup technique. This research method uses a true experiment. The use of bold makeup techniques with secondary colors is the independent variable in this study, while the results of party makeup are the dependent variable. Data analysis techniques used the average value and one-way ANOVA on SPSS 26. The results of the first study, the difference in party makeup results using the average value with X1 (orange-orange-orange) getting a value of 3.26, X2 (purple-purple-purple) getting a value of 3.21 and X3 (green-orange-purple) getting a value of 2.94. The results of the second study, the highest value was obtained by X1 (orange-orange-orange) based on several aspects of the assessment, namely the suitability of the makeup color with the model's skin tone, makeup harmony, neatness of the makeup, and durability of the makeup results. Conversely, the lowest value was achieved by X3 (green-orange-purple), with almost all aspects of the assessment lower than X1 (orange-orange-orange) and X2 (purple-purple-purple). Based on the results of the One Way ANOVA analysis, there was a significant difference between the groups being compared (F(2, 87) = 4.510, p = 0.014). The Sum of Squares value between groups is 63.489 with degrees of freedom (df) 2, while the Sum of Squares value within groups is 612.300 with degrees of freedom 87. The total Sum of Squares is 675.789 with a mean square between groups of 31.744 and within groups of 7.038. Keywords: secondary colors, bold makeup techniques, party makeup results